Dual versus triple therapy of Helicobacter pylori infection: results of a multicentre trial. Issue 1 (1st July 1999) - Behrens, Rolf; Lang, Thomas; Keller, Klaus M; Bindl, Lutz; Becker, Michael; Rodeck, Burkhard; Küster, Peter; Wündisch, Gerhard F; Stolte, Manfred
Abstract : OBJECTIVE: To compare dual therapy (omeprazole and amoxicillin) with triple therapy (omeprazole, amoxicillin, and clarithromycin) in the treatment of Helicobacter pylori infection. The efficacy of 1 mg/kg/day omeprazole was randomly compared with 2 mg/kg/day. STUDY DESIGN: 252 patients (median age, 11.0 years; range, 3–18) presenting with chronic abdominal pain underwent endoscopy and a 13 C-urea breath test. Gastric biopsy specimens were taken for histological examination and for the rapid urease test. Patients were treated for two weeks: group A (n = 63) received amoxicillin (50 mg/kg; maximum, 2 g/day), group B (n = 73) received amoxicillin and clarithromycin (20 mg/kg; maximum, 1 g/day). Both groups were randomly treated with either 1 or 2 mg/kg omeprazole (maximum, 80 mg/day). Diagnostic procedures were repeated four weeks after the end of treatment. RESULTS: 11 patients were excluded; 136 patients were H pylori positive (56%), 105 of whom were re-examined after treatment. Helicobacter pylori was eradicated in 52% of group A and 83% of group B. The dose of omeprazole had no influence on the eradication rate. Specificity and sensitivity of the rapid urease test were 94% and 93%, respectively. Specificity and sensitivity of the 13 C-urea breath test were 93% and 95%, respectively. CONCLUSIONS: Dual therapy can no longer be recommended. Triple therapy is more effective than dual therapy in the eradication of H pylori infection. The lower dose of 1 mg/kg omeprazole was as effective as 2 mg/kg.